Biophilia: 10 Years Later: Nicola Dibben, in a conversation with Martin Guerpin - Dibben, Nicola; Guerpin, Martin (Circuit)

(untitled) (Circuit, musiques contemporaines, 2021)
Prof. Nicola Dibben (University of Sheffield) has published the first academic book on Björk (Björk, London, Equinox Publishing, 2009) and was deeply involved in the making of the multi-media app album Biophilia (2011), which was also designed as a pilot educational project. This conversation takes place ten years after the release of Biophilia and focuses on its impact after 2011. Martin Guerpin and Prof. Dibben tackle the impact of Biophilia in Björk’s post-2011 artistic output. They address three topics: 1) Björk’s engagement with musicology; 2) the impact and results of alternative pedagogical initiatives linked with the Biophilia project; and 3) the place of app-albums like Biophilia in the music industry since 2011.